ANALISIS PENGUNGKAPAN INTELLECTUAL CAPITAL BERDASARKAN PROFITABILITAS, LEVERAGE, DAN SIZE PERUSAHAAN (PERBANDINGAN ANTARA PERUSAHAAN PERBANKAN DI INDONESIA DAN THAILAND - Dimaz Ramananda; Yeterina Widi Nugrahanti (Dinamika Akuntansi Keuangan dan Perbankan, 2014)
The objective of this study is to compare the level of intellectual capital disclosure in any banking company in Indonesia and Thailand listed on the Indonesia Stock Exchange ( IDX ) and the Securities Exchange of Thailand ( SET ) in 2011 based in the characteristics of the company. The variables used in this study is the level of intellectual capital disclosure and corporate characteristics represented by profitability, leverage, and the size of the company. The sample used consists of 39 banks listed on the BEI and 11 banks listed on the SET in 2011. The findings in this study showed no difference between intellectual capital disclosure in Indonesia and Thailand. Keywords : intellectual capital disclosure, profitability, leverage, company size